2021
DOI: 10.1111/jfpp.15862
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new type of Anhua black tea and its application: Black tea wine

Abstract: Tea has been traditionally and widely consumed in China; black tea is among the six types of tea consumed in China (Görkem et al., 2021) and is processed through deep fermentation (Zhang, Wang,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Xia et al [ 105 ] found that ultrasonic treatment was superior to traditional methods in extracting tea polyphenols, caffeine, theanine, and aromatic compounds. In their research, Qin et al [ 106 ] employed ultrasonic techniques to produce a rice-flavored tea wine using Anhua black tea, which was enriched with probiotics to decrease blood lipid levels. The investigation revealed that ultrasonic parameters such as time, solid/liquid ratio, temperature, and power had an impact on the polyphenol concentration of the black tea wine.…”
Section: The Impact Of Ts On the Bioactive Compounds Present In Foodmentioning
confidence: 99%
“…Xia et al [ 105 ] found that ultrasonic treatment was superior to traditional methods in extracting tea polyphenols, caffeine, theanine, and aromatic compounds. In their research, Qin et al [ 106 ] employed ultrasonic techniques to produce a rice-flavored tea wine using Anhua black tea, which was enriched with probiotics to decrease blood lipid levels. The investigation revealed that ultrasonic parameters such as time, solid/liquid ratio, temperature, and power had an impact on the polyphenol concentration of the black tea wine.…”
Section: The Impact Of Ts On the Bioactive Compounds Present In Foodmentioning
confidence: 99%
“…Wang et al demonstrated that the fermented tea contained epigallocatechin gallate, epigallocatechin, and chlorogenic acid, which inhibit lipogenesis in mature 3T3-L1 adipocytes by stimulating adipose decompose ( 73 ). Qin et al fermented Anhua black tea with Monascus and Cystaphylococcus coronatum , resulting in many active substances in the fermented products, such as lovastatin, which had certain lipids lowering effects ( 74 ). Therefore, long-term drinking of microbial fermentation tea has a good role in medical care.…”
Section: Changes Of Biological Activity In Tea After Microbial Fermen...mentioning
confidence: 99%
“… 3 According to the brewing process, tea wines can be categorized into three groups such as sparkling, prepared, and fermented. The research mainly focuses on optimizing rice 4 and composite tea wines. 5 , 6 However, the studies on the fermentation of tea wine using pure tea juice have only analyzed the chemical composition, but no studies on the taste of tea wine are being reported.…”
Section: Introductionmentioning
confidence: 99%